Superparamagnetic electrospun microrods for magnetically-guided pulmonary drug delivery with magnetic heating - Nikolaou, Maria; Avraam, Kyriakos; Kolokithas-Ntoukas, Argiris; Bakandritsos, Aristides; Lizal, Frantisek; Misik, Ondrej; Maly, Milan; Jedelsky, Jan; Savva, Ioanna; Balanean, Florica; Krasia-Christoforou, Theodora (Materials science & engineering. C, Materials for biological applications, 2021)
Controlled pulmonary drug delivery systems employing non-spherical particles as drug carriers attract considerable attention nowadays. Such anisotropic morphologies may travel deeper into the lung airways, thus enabling the efficient accumulation of therapeutic compounds at the point of interest and subsequently their sustained release. This study focuses on the fabrication of electrospun superparamagnetic polymer-based biodegradable microrods consisting of poly(l-lactide) (PLLA), polyethylene oxide (PEO) and oleic acid-coated magnetite nanoparticles (OA·Fe3O4). The production of magnetite-free (0% wt. OA·Fe3O4) and magnetite-loaded (50% and 70% wt. Fe3O4) microrods was realized upon subjecting the as-prepared electrospun fibers to UV irradiation, followed by sonication. Moreover, drug-loaded microrods were fabricated incorporating methyl 4-hydroxybenzoate (MHB) as a model pharmaceutical compound and the drug release profile from both, the drug-loaded membranes and the corresponding microrods was investigated in aqueous media. In addition, the magnetic properties of the produced materials were exploited for remote induction of hyperthermia under AC magnetic field, while the possibility to reduce transport losses and enhance the targeted delivery to lower airways by manipulation of the airborne microrods by DC magnetic field was also demonstrated.
Keywords: Biodegradable microrods; lékové transportní systémy; plíce; Magnetite Nanoparticles; Magnetic field; Magnetic Phenomena; vytápění; Superparamagnetic fibers; Pulmonary drug delivery; Drug Delivery Systems; magnetické jevy; Electrospinning; Lungs; magnetické nanočástice; Magnetics; Magnetic hyperthermia; magnetismus; Heating; Human airways; Lung